Depression, immune function, and early adrenarche in children. (January 2016) - Delany, Faustina M.; Byrne, Michelle L.; Whittle, Sarah; Simmons, Julian G.; Olsson, Craig; Mundy, Lisa K.; Patton, George C.; Allen, Nicholas B.
Highlights: It is yet unclear if a depression-immunity relationship exists in children. Timing of adrenarche may be a moderator of this relationship. Depression and immunity were measured in late vs. early adrenarcheal developers. C-reactive protein was associated with self-reported depressive symptoms. Adrenarche moderated the relation of depression and secretory immunoglobulin A. Abstract: Despite consistent findings of an association between depression and immunity in adult and adolescent populations, little is known about the nature of this relationship at earlier ages. Studies of children have yielded mixed results, suggesting methodological confounds and/or the presence of significant moderating factors. Timing of adrenarche, the first phase of puberty that occurs during late childhood, is a plausible moderator of the depression-immunity relationship in late childhood due to its associations with both the immune system and psychological wellbeing. We hypothesized that: (1) a depression-immunity association exists in children, (2) this association is moderated by adrenarcheal timing, and, (3) this association is also moderated by gender. Data were drawn from a nested study of 103 participants (62 females, M age = 9.5, age range: 8.67–10.21 years) participating in a population based cohort study of the transition from childhood to adolescence (across puberty). Participants in this nested study completed the Children's Depression Inventory 2 (CDI-2) and provided morning saliva samples to measure immune markers (i.e., C-reactive protein, CRP; and secretory immunoglobulin A, SIgA). Using hierarchical regression, inflammation measured by CRP was positively associated with the negative mood/physical symptoms (NM/PS) subscale ( β  = 0.23, t  = 2.33, p  = 0.022) of the CDI-2. A significant interaction effect of SIgA x adrenarcheal timing was found for NM/PS ( β  = −0.39, t  = −2.19, p  = 0.031) and Interpersonal Problems ( β  = −0.47, t  = −2.71, p  = 0.008). SIgA and NM/PS were positively associated for relatively late developers. SIgA and Interpersonal Problems were positively associated for late developers, and negatively associated for early developers. We suggest that both sets of findings might be partially explained by the immunosuppressive effect of the hormonal changes associated with earlier adrenarche, namely testosterone. These results also suggest that adrenarcheal timing has an effect on the association between depression and immunity, and is therefore an important measure in research with younger populations. Future research should utilize longitudinal designs to demonstrate direction of influence of variables, and use a broader range of pro- and anti-inflammatory markers.